Pemeliharaan Saluran Drainase Di Desa Sumber Agung - Rajiman; Hery Riyanto; Susilowati; Any Nurhasanah (AMMA : Jurnal Pengabdian Masyarakat, 2022)
The canal is one of the complementary buildings on the road segment in meeting the technical requirements of road infrastructure. The highway channel serves to circulate air that can interfere with road users, so that the road body remains dry. This research was conducted in Sumber Agung Village, Kemiling District, Bandar Lampung City on September 17, 2021. This research method is descriptive qualitative. The purpose of this study is to explain to the public what is meant by a drainage system and explain how the procedures for a good road drainage system are to prevent this from happening in the road area. The conclusion of this study is that rural problems are problems that have a fairly high complexity so that a comprehensive and sustainable solution is needed. The participation of local communities in the implementation of community empowerment is still low due to the lack of public awareness in maintaining drainage channels.